1997
DOI: 10.1021/es961058+
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Binary and Ternary Citric Acid Complexes of Iron and Uranium

Abstract: Citric acid forms ternary mixed-metal complexes with various metal ions involving the hydroxyl and carboxyl groups of citric acid. The coordination of the metal to citric acid has been shown to affect the biodegradation of the metal−citrate complexes and metal mobility in the environ ment. We investigated the formation and biodegradation of the ternary mixed metal Fe−U−citric acid complex. The presence of 1:1:2 Fe−U−citric acid in solution was confirmed by potentiometric titration, UV−vis spectrophotometry, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…The major bioavailable forms of U(VI) are likely UO 2 2þ and UO 2 OH þ rather than uranium complexed or adsorbed to colloidal or particulate matter (unpublished data). U(VI) complexed with inorganic ligands (e.g., carbonate, sulfate, or phosphate) and humic substances apparently reduce the bioavailability of uranium by reducing the activity of UO 2 2þ and UO 2 OH þ (Kohler et al, 1996;Dodge and Francis, 1997;Markich, 2002).…”
Section: Interactions Of Uranium Ions and Phosphate In The Mediummentioning
confidence: 99%
“…The major bioavailable forms of U(VI) are likely UO 2 2þ and UO 2 OH þ rather than uranium complexed or adsorbed to colloidal or particulate matter (unpublished data). U(VI) complexed with inorganic ligands (e.g., carbonate, sulfate, or phosphate) and humic substances apparently reduce the bioavailability of uranium by reducing the activity of UO 2 2þ and UO 2 OH þ (Kohler et al, 1996;Dodge and Francis, 1997;Markich, 2002).…”
Section: Interactions Of Uranium Ions and Phosphate In The Mediummentioning
confidence: 99%
“…Citric acid forms ternary mixedmetal complexes with various metal ions involving the hydroxyl and carboxyl groups of citric acid. The presence of 1:1:2 Fe:U:citric acid in solution was confirmed by potentiometric titration, UV-vis spectrophotometry, gel-filtration chromatography, and extended X-ray absorption fine structure (EXAFS) analysis (Dodge and Francis, 1997). Comparison of the EXAFS spectra show the 1:1:2 Fe:U:citric acid complex has structural characteristics similar to the 1:1 U:citric acid complex.…”
Section: Biotransformation Under Aerobic Conditionsmentioning
confidence: 87%
“…However, with two-fold excess citric acid, a 1:1:1 Fe:U:citric acid complex remained in solution after the excess citric acid was biodegraded. These results suggest that similar to the U-citrate complex, the Fe-U-citrate complex is recalcitrant to biodegradation (Dodge and Francis, 1997). The persistence of mixedmetal-citrate complexes in wastes and contaminated environments may result in the mobilization of uranium.…”
Section: Biotransformation Under Aerobic Conditionsmentioning
confidence: 89%
“…After a lag period of 34-h, citrate was completely utilized at the rate of 68.18 ± 3.42 mol/h within 44 h. Solution pH increased from 6.1 to 9.1, metals were almost completely removed from solution at the end of the experiment. These results suggested that recalcitrant mixed-metal-citrate complex was not formed [18], and the presence of Fe 3+ and Zn 2+ jointly caused the biotransformation of Cd-citrate complex in the 1:1:1:3 Fe:Zn:Cd:citrate medium.…”
Section: Effect Of Fe 3+ or Zn 2+ On Biotransformation Of Cd-citrate mentioning
confidence: 89%
“…At the end of the incubation, more than 98% of the metals were removed from the two media. The completely metabolism of citrate indicated that nonbiodegradable mixed-metal-citrate complexes were not formed in these media [18]. The results also revealed that the presence of Fe 3+ or Zn 2+ resulted in complete transformation of Cd-citrate complex, respectively.…”
Section: Effect Of Fe 3+ or Zn 2+ On Biotransformation Of Cd-citrate mentioning
confidence: 91%